The Effects of Mergers on Prices, Costs, And Capacity Utilization in the U.S. Air Transportation Industry, 1970-84 - Frank R. Lichtenberg; Moshe Kim (Levy Economics Institute of Bard College, 1989)
We analyze the effect of mergers on various aspects of airline performance during the period 1970-84, using a panel data set constructed by Caves et al. Estimates derived from a simple "matched pairs" statistical model indicate that these mergers were associated with reductions in unit cost. The average annual rate of unit cost growth of carriers undergoing merger was 1.1 percentage points lower, during the five-year period centered on the merger, than that of carriers not involved in merger. Almost all of this cost reduction appears to have been passed on to consumers. Part of the cost reduction is attributable to merger-related declines in the prices of inputs, particularly labor, but about two-thirds of it is due to increased total factor productivity. One source of the productivity improvement is an increase in capacity utilization (load factor).
Keywords: 330